Measurement delay associated with the Guardian® RT continuous glucose monitoring system - Wei, C.; Lunn, D. J.; Acerini, C. L.; Allen, J. M.; Larsen, A. M.; Wilinska, M. E.; Dunger, D. B.; Hovorka, R. (Diabetic medicine, 2010)
Diabet. Med. Aims  Using compartment modelling, we assessed the time delay between blood glucose and sensor glucose measured by the Guardian® RT continuous glucose monitoring system in young subjects with Type 1 diabetes (T1D). Methods  Twelve children and adolescents with T1D treated by continuous subcutaneous insulin infusion (male/female 7/5; age 13.1 ± 4.2 years; body mass index 21.9 ± 4.3 kg/m2; mean ± sd) were studied over 19 h in a Clinical Research Facility. Guardian® RT was calibrated every 6 h and sensor glucose measured every 5 min. Reference blood glucose was measured every 15 min using a YSI 2300 STAT Plus Analyser. A population compartment model of sensor glucose–blood glucose kinetics was adopted to estimate the time delay, the calibration scale and the calibration shift. Results  The population median of the time delay was 15.8 (interquartile range 15.2, 16.5) min, which was corroborated by correlation analysis between blood glucose and 15‐min delayed sensor glucose. The delay has a relatively low intersubject variability, with 95% of individuals predicted to have delays between 10.4 and 24.3 min. Population medians (interquartile range) for the scale and shift are 0.800 (0.777, 0.823) (unitless) and 1.66 (1.47, 1.84) mmol/l, respectively. Conclusions  In young subjects with T1D, the total time delay associated with the Guardian® RT system was approximately 15 min. This is twice that expected on physiological grounds, suggesting a 5‐ to 10‐min delay because of data processing. Delays above 25 min are rarely to be observed.